Interactive School-Based Reproductive Health Education to Improve Adolescents' Knowledge: A Community Engagement Experience - Dewi Novitasari Suhaid; Dyah Woro Kartiko Kusumo Wardani; Mitra Kadarsih (Universitas Ibn Khaldun, 2026)
Background: adolescents require accurate reproductive health information to support healthy physical and psychosocial development. However, misconceptions and limited access to age-appropriate education remain common. Situation analysis: students at SMP “X”, South Tangerang, demonstrated varying levels of knowledge regarding puberty, menstruation, nocturnal emissions, personal hygiene, and reproductive health. Problem: inadequate reproductive health literacy may increase adolescents' vulnerability to unhealthy behaviors and misconceptions during puberty. Solution: A school-based community engagement program was conducted using interactive educational strategies, including audiovisual presentations, educational videos, group discussions, and Kahoot based quizzes. The sessions were delivered separately for male and female students to facilitate open discussion of gender-specific topics. Results: A total of 116 students participated in the program. Knowledge improved in both groups, with a mean increase of 37.6% among male students and 38.0% among female students. Female participants also demonstrated a high prevalence of menarche and dysmenorrhea, highlighting the importance of menstrual health education. Conclusion: Interactive, school based reproductive health education effectively improved adolescents' knowledge and engagement. Integrating age-appropriate reproductive health education into routine school health programs may strengthen adolescents' health literacy and promote healthier behaviors.